Setting targets for antibiotic use in general practice in Europe: A scoping review - Nathaly Garzón-Orjuela; Kevin Roche; Heike Vornhagen; Aoife Moran; Scott Walkin; Walter Cullen; Catherine Blake; Akke Vellinga (European Journal of General Practice)
Background National Action Plans (NAPs) aim to address antimicrobial resistance (AMR) understanding and awareness but struggle to translate targets into clinically relevant guidance for general practice.Objective To identify and map antibiotic use targets in European general practice and explore if and how these targets are linked to NAPs.Methods A systematic search was carried out in MEDLINE (OVID), EMBASE and SCOPUS, with additional manual searches. The research questions were: What are existing targets for antibiotic use in general practice in the 31 European countries? and How are these targets linked to the NAPs on AMR?. The results are presented narratively.Results 77 reports were included, of which 33 focused on national targets and general practice or linking national and local targets. Reports describe local strategies to achieve targets, such as prescriber feedback, benchmarking systems and financial incentives. However, these reports provide aggregated targets for general practice, such as a percentage reduction of antibiotics prescribed. These targets are set in general, for a specific type of antibiotic, for an amount per number of patients, in defined daily doses or items. None of the reports translate national targets into clinically relevant or practical targets for general practitioners.Conclusion Most European countries have an NAP with established targets, but the type and implementation of these targets vary between nations. Translating national targets into daily clinical practice is challenging and often lacks the involvement of prescribers. Aligning national and local targets would enhance coherence and more effectively contribute to improvements in antibiotic use.